CEO Duality as a Double-Edged Sword: How Boards of Directors Balance Entrenchment Avoidance and Unity of Command - Finkelstein, Sydney; D'Aveni, Richard A. (Academy of Management Journal, 1994)
When a firm's chief executive officer is also the chairperson of its board, directors have opposing objectives. According to organization theory, such CEO duality establishes strong, unambiguous leadership. But according to agency theory, duality promotes CEO entrenchment by reducing board monitoring effectiveness. We developed a contingency framework to resolve these perspectives. Sampling three industries to enhance generalizability, we found that board vigilance was positively associated with CEO duality. Duality was less common, however, when CEOs had high informal power and when firm performance was high.